Kepemimpinan Efektif Kepala Sekolah Menengah Pertama Negeri 1 Mijen Kabupaten Demak dalam Pencapaian Prestasi - Intan Puspita Nugraheni (Jurnal Kualita Pendidikan, 2022)
The focus of this research is 1) how is the effective leadership of the head of SMP Negeri 1 Mjen Demak Regency in achieving achievement, 2) how is the effective leadership strategy of the head of SMP Negeri 1 Mijen Demak Regency in achieving achievement, and 3) how are the efforts made by the principal when facing obstacles to leadership. The approach used in this research is descriptive qualitative, sampling is done purposively and snowball, data collection technique is done by triangulation, and data analysis is inductive/qualitative. The results showed that 1) the implementation of effective leadership by the principal of SMP Negeri 1 Mijen can be seen from a) the principal manages school management according to management principles, b) the principal carries out his leadership by paying attention to the maturity of subordinates not seniority, and c) the principal has succeeded in bringing the school and students achieve achievement; 2) effective leadership of the head of SMP Negeri 1 Mijen, Demak Regency in achieving achievements through two stages of strategy, namely a) the diagnosis stage, and b) the strategy formulation stage; and 3) efforts made by school principals when facing obstacles in their leadership include a) principals empowering school committees and other parties, b) building a conducive work climate, and gathering support from the community and government, c) maximizing the management of facilities and infrastructure, d) maximize the division of tasks and intervene directly to help the difficulties of employees, and e) to overcome problems for students, the principal prioritizes dialogue to find solutions. Suggestions that can be submitted include, among others, the principal should be able to mobilize all his subordinates to carry out school programs, improve the reputation of good administration in all fields, and propose the addition of new PNS/PTT to overcome the shortage of existing personnel.